2015
DOI: 10.1586/14787210.2015.1068118
|View full text |Cite
|
Sign up to set email alerts
|

Glycopeptide antibiotics: evolving resistance, pharmacology and adverse event profile

Abstract: The first glycopeptide antibiotic was vancomycin, isolated from the soil in the 1950s; since then, the class has expanded to include teicoplanin and the new semisynthetic glycopeptides dalbavancin, oritavancin and telavancin. They are bactericidal, active against most Gram-positive organisms, and in a concentration-dependent manner, inhibit cell wall synthesis. Resistance to vancomycin has emerged, especially among enterococci and Staphylococcus aureus through a variety of mechanisms. This emerging resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 104 publications
(107 reference statements)
0
8
1
3
Order By: Relevance
“…It is interesting that the same dependence in antimicrobial activity was demonstrated by the reference positive control, vancomycin, which belongs to the group of glycopeptide antibiotics [ 14 ] and is structurally dissimilar to emericellipsin A. The same effect was demonstrated for peptaibol emerimicin IV, which was isolated from Emericellopsis minima and displays bactericidal activity towards methicillin-resistant S. aureus and vancomycin-resistant Enterococcus faecalis (Gram-positive species); Gram-negative E. coli was resistant [ 15 ].…”
Section: Resultsmentioning
confidence: 91%
“…It is interesting that the same dependence in antimicrobial activity was demonstrated by the reference positive control, vancomycin, which belongs to the group of glycopeptide antibiotics [ 14 ] and is structurally dissimilar to emericellipsin A. The same effect was demonstrated for peptaibol emerimicin IV, which was isolated from Emericellopsis minima and displays bactericidal activity towards methicillin-resistant S. aureus and vancomycin-resistant Enterococcus faecalis (Gram-positive species); Gram-negative E. coli was resistant [ 15 ].…”
Section: Resultsmentioning
confidence: 91%
“…Contribution of CL CVVHDF to CL TOTAL was 51.2 ± 23.6%. Considering the elimination half‐life in normal kidney function is 70–100 h, the amount of teicoplanin eliminated in CVVHDF seems to be not dominant to remove the drug from circulation. However, the T 1/2 of 100.1 ± 42.7 hours was lower than that in patients with chronic renal insufficiency (157–567 h), suggesting that higher amounts of teicoplanin could be removed by CVVHDF.…”
Section: Discussionmentioning
confidence: 99%
“…[18] So far,m ore than 4000 halometabolites have been discovered, [19] including commercially important antibiotics, such as chloramphenicol, [20] vancomycin, [21] and teicoplanin. [22] The presence of the tryptophan-halogenase-encoding gene (ADW94630.1) within the NRPS gene cluster was discovered in the genome sequence of Streptomyces toxytricini (NRRL 15443). [23] Aheterologous expression experiment indicated that the function of this gene was to induce chlorination at 6th positiono ft he tryptophan (Trp) indole group.…”
Section: Introductionmentioning
confidence: 99%